Orienting Toward Possibility: Girls and Bisexuality at School. Issue 2 (December 2021) - Mamo, Laura; Fields, Jessica; Gilbert, Jen; Pereira, David
While many more high school girls identify as bisexual than as lesbian, queer, or other marginalized sexual identities, girls who identify as bisexual remain peripheral to sexuality research and to many sexual health education programs. Nevertheless, research suggests that bisexuality is a distinct claim and experience for girls, marked by highly gendered discourses of sexuality and queerness. Based on the Beyond Bullying Project, a multimedia storytelling project that invited students, teachers, and community members in three U.S. high schools to enter a private booth and share stories of LGBTQ (lesbian, gay, bisexual, transgender and queer or questioning) sexuality and gender, this article explores the work the identity "bisexual" and the category "bisexuality" accomplish for girls when claimed for themselves or another or put into circulation at school. We consider the range of meanings and identifications mobilized by bisexuality and, drawing on insights of critical narrative intervention, explore how sexual health and sexuality educators might receive girls' narratives of bisexuality as capacious and contradictory—as claims to identity, as uncertain gestures toward desire, and as assertions of possibility and resistance. We show that in the assertion of bisexuality, girls align themselves with the surprise of desire and position themselves to resist the disciplining expectations of heteronormative schooling. Critical narrative intervention, with its focus on using stories to challenge the status quo, allows educators and researchers to recognize in girls' stories of bisexuality, the potential of new approaches to sexual health education and social belonging.